Impact of the Covid 19 Pandemic on Small and Medium Enterprises (SMEs) Performance: A Qualitative Study in Indonesia - Setyoko, Paulus Israwan; Kurniasih, Denok (Journal of Industrial Engineering & Management Research, 2022)
The COVID-19 pandemic has an impact on the economy, social and politics, not only large countries but almost all countries in the world. Indonesia, which is dominated by Micro, Small, and Medium Enterprises (SMEs) needs to pay special attention to this sector because the contribution of SMEs to the national economy is quite large. This type of research is qualitative research through interviews and literature, namely in the process of collecting data, taking various reference sources that support this research. The results of this study are to determine the economic and business challenges due to the COVID-19 pandemic and the approaches taken, namely the macro approach, and the micro approach. The purpose of this study is to analyze the impact of the COVID-19 pandemic on the existence of SMEs in Indonesia and how solutions can help SMEs survive in the COVID-19 pandemic situation. The impact of Covid-19 has had a considerable impact on the economy in Indonesia, especially SMEs. By properly managing business cycle management and changing business models and digital transformation by adjusting to the conditions of the COVID-19 pandemic, it is hoped that the SME company’s strategy will be able to successfully overcome the challenges. The synergy between the government’s macro policies and the company’s micro policies is expected to help SMEs in overcoming the challenges of facing the COVID19 pandemic crisis.